2020
DOI: 10.1155/2020/8865748
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Water Diffusion Mechanism on Mechanical Properties of Polypropylene Composites

Abstract: This study evaluates the water diffusion mechanism on mechanical properties of polypropylene reinforced composites. Compounding of the composites into sheets was carried out using the compression moulding techniques by incorporating varying weight percentage of fibers and polypropylene. Mechanical properties of the composites were assessed according to ASTM standards, while the composite fracture surface was examined using a scanning electron microscope. The water absorption behaviour and diffusion mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…Similar type of observation of water diffusion was reported by Balogun et al. 34 On increasing the soaking time, epoxy and all the bionanocomposites obtained their saturation stage after 28 days of soaking time. It is very interesting to observe that all the bionanocomposites have very less water uptake (i.e.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Similar type of observation of water diffusion was reported by Balogun et al. 34 On increasing the soaking time, epoxy and all the bionanocomposites obtained their saturation stage after 28 days of soaking time. It is very interesting to observe that all the bionanocomposites have very less water uptake (i.e.…”
Section: Resultssupporting
confidence: 87%
“…Balogun et al. 34 observed that the tensile strength of Entada mannii fiber-reinforced polypropylene composites was significantly reduced compared to dry specimen by water uptake credited to an increase in fibers loading causing poor fiber–matrix interfacial bonding. In some other studies, a reduction in the tensile properties of biocomposites as a result of water uptake was also reported.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 10 , the behavior of the composite materials obtained does not conform to the Fickian diffusion mechanism curve but rather resembles a non-Fickian or anomalous behavior [ 74 ]. Table 6 shows the kinetic parameters slope and intercept, as well as the degree of linear correlation of the curve.…”
Section: Resultsmentioning
confidence: 99%
“…However, acrylic thermoplastic composites, as well as other polymeric matrices reinforced with natural fibers, have drawbacks such as limited processing temperature, lack of compatibility between fiber and matrix, low fire resistance, and high water absorption [ 7 , 17 ]. The latter is a critical parameter in the performance of these composites, since water absorption usually produces poor adherence between the matrix and fibers, poor stress transfer, matrix degradation, and dimensional instability [ 21 , 22 , 23 ]. The water absorption in thermoplastic matrix composites reinforced with natural fibers is mainly related to the chemical composition and microstructure of natural fibers [ 21 ].…”
Section: Introductionmentioning
confidence: 99%